Simplistic thermal transformation of MIL-125 to TiO2 nano-coins and nano-diamonds for efficient quantum-dot sensitized solar cells. (December 2019) - Basit, Muhammad Abdul; Rashid, Muhammad; Khan, Talha Farooq; Muhyuddin, Mohsin; Butt, Sajid
Abstract: TiO2 -based nano-coins and nano-diamonds were successfully incorporated for improved performance of PbS quantum-dot sensitized solar cells (QDSCs) through a simplistic thermal transformation of NH2 -MIL-125(Ti). We report a modified heat-treatment process which affirms simple transformation of NH2 -MIL-125(Ti) to TiO2 in addition to the removal of organic constituents of screen-printed TiO2 photoanoade, eliminating the discrete heat-treatment cycle for thermal transformation of NH2 -MIL-125(Ti) before screen-printing. X-ray diffraction spectroscopy (XRD) revealed the phase transformation and resultant crystal structures of TiO2 while XPS was used to authenticate the fabrication of PbS sensitized TiO2 photoanode. UV–Vis spectroscopy showed that the modified photoanodes with TiO2 nano-coins and nano-diamonds exhibited improved reflectance of light, which resulted in enhanced visible light absorbance in PbS QDs. Relatively, incorporation of simplistically transformed TiO2 nano-diamonds resulted higher photocurrent density ( J SC ~17 mA/cm 2 ) in QDSCs which was credited to superior absorbance of incident light and inferior charge carrier recombination. Graphical abstract: Image 1 Highlights: Thermally simplistic transformation of NH2 -MIL-125(Ti) to TiO2 is realized. In-depth XPS analysis authenticated the effectuality of modified thermal transformation. Nanostructured TiO2 coins and diamonds originated improvement in absorbance of light. Thus, higher Jsc, PCE and OCVD characteristics were exhibited by PbS-based QDSCs.